Distributions, sources, and air-sea fluxes of nitrous oxide in Bohai Bay, China - Wang, Zhi; Gu, Ting; Wen, Yujian; Cui, XuDong; Jia, Dai; Sun, Jun (Frontiers in Marine Science, 2023)
Shallow seas are the main source of worldwide N₂O emissions. It is highly influenced by human activities and is of great scientific importance. Two cruises were conducted in Bohai Bay in 2020, collecting N₂O samples from 56 stations, measuring and calculating the dissolved N₂O concentration and sea-air emission flux. The concentration of N2O tended to decrease in a graduation from the estuary to the continental shelf during the summer, that was influenced by river input; in the autumn, that was influenced by the combined effect of seawater, the N2O distribution was uniform. It was found that the concentration of dissolved N₂O varied considerably in time and spatial distribution. The range in summer was from 21.5 to 59.8 nmol/L with an average concentration of 32.5 ± 6.9 nmol/L, while the dissolved concentrations in the autumn voyage ranged from 14.9 to 75.8 nmol/L with an average concentration of 23.1 ± 6.34 nmol/L. Rivers had an impact on Bohai Bay in the summer, and the horizontal distribution of the N₂O concentrations showed a radial pattern. In contrast, the monsoon has a greater impact in the autumn and the horizontal distribution of N₂O concentrations is more uniform. Because Bohai Bay is shallowly submerged and the seawater is thoroughly mixed, the N₂O content did not vary significantly along the vertical distribution. The average dissolved concentration in autumn was lower than that in summer, because the precipitation in autumn was reduced, and the amount of river input was lower than that in summer. At the same time, we observed different phenomena in the estuarine region of the Hai River. The average flux of nitrous oxide was higher in autumn than in summer, with an average flux of 3.4 ± 1.9 μmol m-2 d-1 in summer and 96 ± 95 μmol m-2 d-1 in autumn, which is caused by the monsoon influence on Bohai Bay, where the wind speed is much higher in winter than in summer. The analysis of the dissolved oxygen environment in Bohai Bay shows that N2O in Bohai Bay is mainly generated through nitrification reactions.